2001
DOI: 10.1080/02701367.2001.10608928
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Decision Making for Baseball Pitch Recognition: Using P300 Latency and Amplitude to Index Attentional Processing

Abstract: This study was designed to examine the perceptual and attentional processes associated with the effects of administering a cost-benefit precuing paradigm to intermediate and advance-level baseball batters. Psychophysiological and performance data obtained from 10 advanced and 10 intermediate-level players were compared. A total of 400 pitches (200 fastballs, 200 curveballs) was randomly presented via a large projection screen, and participants pressed one of two buttons to indicate the type of pitch thrown. Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 38 publications
3
41
0
6
Order By: Relevance
“…Although EEG measures have several limitations for the study of attention in sport, such as the requirement of minimal movement, poor concordance with other measures of attention, expense, and poor portability, they have nevertheless been successfully utilized in several sports, especially aiming sports such as rifle shooting (Hatfield, Landers, & Ray, 1984;Janelle et al, 2000;Rossi & Zani, 1991) and archery (Landers et al, 1994), baseball (Radlo, Janelle, Barba, & Frehlich, 2001), and self-paced skills such as golf putting (Crews & Landers, 1993). Integration of measurement techniques seems a logical strategy for assessing attentional workload at multiple levels (Abernethy, Summers, & Ford, 1998;Wilson & O'Donnell, 1988), consistent with the trend toward multilevel measurement and theorizing in other aspects of psychology and the behavioral sciences (e.g., Cacioppo & Berntson, 1992;McLeod & Driver, 1993).…”
Section: Measuring Attentional Requirementsmentioning
confidence: 99%
“…Although EEG measures have several limitations for the study of attention in sport, such as the requirement of minimal movement, poor concordance with other measures of attention, expense, and poor portability, they have nevertheless been successfully utilized in several sports, especially aiming sports such as rifle shooting (Hatfield, Landers, & Ray, 1984;Janelle et al, 2000;Rossi & Zani, 1991) and archery (Landers et al, 1994), baseball (Radlo, Janelle, Barba, & Frehlich, 2001), and self-paced skills such as golf putting (Crews & Landers, 1993). Integration of measurement techniques seems a logical strategy for assessing attentional workload at multiple levels (Abernethy, Summers, & Ford, 1998;Wilson & O'Donnell, 1988), consistent with the trend toward multilevel measurement and theorizing in other aspects of psychology and the behavioral sciences (e.g., Cacioppo & Berntson, 1992;McLeod & Driver, 1993).…”
Section: Measuring Attentional Requirementsmentioning
confidence: 99%
“…Such a limitation on the nature of the tasks studied has been restrictive, but studies are beginning to appear in the literature in which cortical responses have been examined during such reactive sport situations as baseball batting and table tennis performance. Radlo, Janelle, Barba, and Frehlich (2001) recently employed ERP measures to assess decision making in 10 advanced and 10 intermediate baseball players who were presented with a type of oddball task. More specifically, 400 trials consisting of video images of baseball pitches were presented via a large projection screen (200 fastball images and 200 curveball images).…”
Section: Brain Processes During Reactive Psychomotor Performancementioning
confidence: 99%
“…However, Ripoll and Latiri (1997) reported that expert athletes in fast-ball sports did not significantly increase their timing errors in trials in which moving targets had unexpected velocity changes (see also Benguigui & Ripoll, 1998;Runigo, Benguigui, & Bardy, 2005). Several studies using other paradigms that induced motor preparation have shown reduced anticipation cost in expert athletes (e.g., Nougier & Rossi, 1999;Nougier, Stein, & Bonnel, 1991;Radlo, Janelle, Barba, & Frehlich, 2001). These results suggested that experts in fast-ball sports may develop some kind of cognitive process to circumvent the anticipation cost of the induced prepared response, but such cognitive processes are not well documented.…”
Section: Introductionmentioning
confidence: 96%